2019
DOI: 10.1158/1078-0432.ccr-18-0803
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Novel Prostate-Specific Membrane Antigen-Targeted Near-Infrared Imaging Agent for Fluorescence-Guided Surgery of Prostate Cancer

Abstract: The ability to locate and remove all malignant lesions during radical prostatectomy leads not only to prevent biochemical recurrence (BCR) and possible side effects but also to improve the life expectancy of patients with prostate cancer. Fluorescence-guided surgery (FGS) has emerged as a technique that uses fluorescence to highlight cancerous cells and guide surgeons to resect tumors in real time. Thus, development of tumor-specific near-infrared (NIR) agents that target biomarkers solely expressed on prostat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…The field of intraoperative fluorescence-guided surgery has been growing vigorously over the last 2 decades and is being used within the clinic more often because of its potential to realize radical resections while preserving healthy tissue (2,21). With this reasoning, numerous fluorescence-based probes for the imaging of prostate cancer have been studied preclinically (22)(23)(24). Although the influence of various families of (commercially available) dyes on the PSMA-targeting ability has been studied (25), systematic refinement of the dye structure intending to tailor PSMA interaction has only been reported by Matsuoka et al, who reported that sulfonation of cyanine dyes had a positive influence on the PSMA affinity (26).…”
mentioning
confidence: 99%
“…The field of intraoperative fluorescence-guided surgery has been growing vigorously over the last 2 decades and is being used within the clinic more often because of its potential to realize radical resections while preserving healthy tissue (2,21). With this reasoning, numerous fluorescence-based probes for the imaging of prostate cancer have been studied preclinically (22)(23)(24). Although the influence of various families of (commercially available) dyes on the PSMA-targeting ability has been studied (25), systematic refinement of the dye structure intending to tailor PSMA interaction has only been reported by Matsuoka et al, who reported that sulfonation of cyanine dyes had a positive influence on the PSMA affinity (26).…”
mentioning
confidence: 99%
“…PSMA immunohistochemical evaluation should be further investigated as a predictive marker in men with metastatic PCa, to guide clinicians in the selection of the most appropriate imaging technique and therapy in individual patients. The choice of emerging PSMA-targeted tracers and therapeutic agents requires further investigation in order to identify the most specific compound for the distinct sites and phases of the disease (8385). As our understanding of the role of PSMA in prostate carcinogenesis advances and molecular techniques become more refined, PSMA-based strategies will have a crucial role in the evolving diagnostic and therapeutic landscape of patients with PCa.…”
Section: Resultsmentioning
confidence: 99%
“…PSMA is often overexpressed by PCa cells, and the ligand can be bound to an infrared fluorescent dye or Cy5 dye. This dye has absorption and emission wavelengths in the NIR and far red ranges, enabling fluorescence imaging using a fluorophore [30,39,40]. PSMA can also be coupled to 68 Gallium, enabling Cerenkov luminescence imaging during surgery using positron emitting properties of 68 Gallium.…”
Section: Alternative and Future Technologiesmentioning
confidence: 99%